Lactobacillus regulate muscle fiber type conversion in Chinese native pigs via tryptophan metabolism - Bo Song; Md. Abul Kalam Azad; Qian Zhu; Yating Cheng; Sujuan Ding; Kang Yao; Xiangfeng Kong (npj Biofilms and Microbiomes)
Abstract Identifying potential gut microbes and metabolites that can influence muscle fiber type is gaining interest in meat quality research. In this study, muscle fiber characteristics, muscle metabolite profiles, and gut microbiota and metabolome were compared among three pig breeds (Taoyuan black, TB; Xiangcun black, XB; and Duroc pigs). The results showed that the slow-twitch fiber percentage was higher (P < 0.05) in native pigs (TB and XB pigs) compared to Duroc pigs. The differences were mainly regulated by Lactobacillus abundance and tryptophan metabolism. Further, fecal microbiota transplantation from XB pigs transferred a higher slow-twitch fiber percentage, Lactobacillus abundance, kynurenic acid level, and AMPK/PGC-1α expression to mice. These findings suggest that Lactobacillus in the colon of TB and XB pigs, through kynurenic acid production, may promote slow-twitch fiber formation via the AMPK/PGC-1α signaling pathway.